Transport and socio-spatial inequalities: the case of the Istanbul Metro - Beyazit, E (2013)
In this thesis, socio-spatial processes regarding the distribution of transport infrastructures are investigated and the ways in which inequalities occur as a result of these processes are discussed. The transport system of Istanbul and particularly, the Istanbul Metro, the first modern subway of the city, has been the focus of this research. In order to understand inequalities in transport, social and spatial justice theories have been employed. Discussions have been extended in order to include different approaches to the issues of transport inequality from various disciplines such as geography, sociology and urban planning. In this sense, this study is multi-disciplinary. Debates on land rent theory, space and power, gendered mobilities, social exclusion and the right to the city are among the many concerns that formed the main arguments of this research. In this thesis, transport is taken as a fixed, an immobile commodity that produces mobile and dynamic commodities such as mobilities and flows. Through such interaction socio-spatial processes are produced which may or may not consist of inequalities. Issues related to inequalities are deconstructed in the literature review in order to help reconstruct a theory of uneven socio-spatial development as a result of the distribution of transport infrastructure investments. Discussions on theory are further examined through four empirical chapters each of which investigates different issues related to transport inequalities. A mixed-method approach has been used in order to fully explore the complexity of the subject and integrate different epistemological positions. Through four empirical chapters, socio-spatial inequalities are discussed with regard to daily mobility levels of different socio-economic groups in Istanbul and the Istanbul Metro as well as in-direct economic impacts of the Metro and the socio-political processes it generates. The findings support some of the previous research on social inequalities based on transport, especially on how gender, education and employment become important determinants of travel time, trip frequency, trip purposes and the use of different transport modes. Yet, the thesis presents unexpected results on the impacts of the Istanbul Metro. On the one hand, the Istanbul Metro can be regarded as a just infrastructure as it accommodates users from every socio-economic background. On the other hand, it can be inequitable as it is likely to facilitate the accumulation of capital in certain areas, and circulation of producers and consumers of this capital within the same spatial unit, the Metro itself. This thesis proposes that horizontal and vertical socio-spatial inequalities exist both individually and together in various contexts in Istanbul. These inequalities are based on the spatial distribution of transport infrastructure investments, power relationships between different socio-economic groups, the dominance of politically powerful groups and the historical development of the urban space. Together this thesis is in an attempt to establish a comprehensive narrative of the discourses of inequalities in transport planning and policy and makes suggestions on the ways to reduce such inequalities. Moreover, this thesis is an original contribution to the literature as it links hitherto unconnected strands of theory in transport geography and social and spatial justice literatures.